Election Fiqh Ethics: Efforts to Prevent Polarization and Its Impact on the 2024 Election - Fauziyah, Ulil; Rozaq, Abd (AJIS: Academic Journal of Islamic Studies, 2024)
Polarization in the implementation of elections, especially in 2024, has a very dangerous impact which has the potential to create divisions between ethnicities, religions, races and between groups. One of the efforts to prevent this and minimize negative impacts is by creating norms from a fiqh perspective considering that the majority is 85 percent of the population. Indonesia is a Muslim society. This research aims to explain election ethics from a fiqh perspective to prevent and minimize polarization in the implementation of the 2024 election and its impacts. By using qualitative descriptive methods and a literature approach, researchers will collect and examine data from various written sources to look for election ethics from a jurisprudential perspective in preventing polarization in the 2024 simultaneous elections. Fiqh ethics in preventing polarization are divided into two, namely universal ethics and partial ethics. Universal ethics include arranging good motivation, not violating existing rules, maintaining human values, bringing benefits and rejecting damage and being fair. Meanwhile, the partial ethics are ta'aruf, tafahum, tasamuh, ta'awun, mujjadi and takaful.